THE IMPACT OF UNDERAGE MARRIAGE ON HOUSEHOLD HARMONY IN BADUY SOCIETY FROM THE PERSPECTIVE OF CUSTOMARY LAW AND MARRIAGE LAW - Suhadi, Aris; Efriyanto, Efriyanto; Muslih, Muhamad (Faculty of Law, Universitas Pekalongan, 2024)
Underage marriage still occurs frequently in Baduy society. As we know, the government has made regulations on the age limit for marriage as a response to several events that have occurred in several households in Indonesia. Several divorces occur because the husband or wife is too young so that in their marriage they are prone to quarrels, so regulations on the age limit for marriage for men and women are made.The researcher formulated the problem of this research, namely whether underage marriage that occurs in Baduy has an impact on marital harmony and household peace in Baduy and how effective is the marriage law regarding the minimum age limit for marriage for the Baduy community.According to the researcher, the purpose of the study is to find out the customary law regulations or considerations in Baduy regarding the age limit for Baduy men and women who will marry.The researcher believes that the long-term goal of this study is to ensure that all parties, both academics and the local government, provide direction, education, and socialization regarding the age limit for marriage in the Baduy community and its surroundings in order to create family harmony in the Baduy community. This is done as long as it does not conflict with Baduy customary law.The specific target of the study is to socialize regulations regarding the age limit for marriage to the wider community so that it is hoped that a sakinah mawadah wa rahmah household will be realized and free from quarrels between husband and wife in Indonesian families in general, and in particular for the Baduy community.Then the researcher uses a method to achieve these goals, namely the normative sociological and normative juridical legal research method, which is descriptive analytical using primary and secondary data sources which are analyzed by the researcher qualitatively. Descriptive in the form of a description of the current conditions of the average age of marriage in marriage in Baduy. Literature study, observation, and Baduy study were conducted to obtain the data needed by the researcher. Interviews with the local government will also be conducted to determine the divorce rate of the Baduy community and the community around Baduy, so that the best efforts can be made to socialize regulations regarding the age limit for marriage.